Acculturative Stress among Asian International Students in Singapore - Nasirudeen, A.M.A.; Koh, Josephine Wat Neo; Lau, Adeline Lee Chin; Seng, Lim Lay; Ling, How Ai (Journal of International Students, 2014)
This study aims to identify the level of acculturative stress and to examine the correlations between acculturative stress or its subcategories and variables such as English language proficiency. The results show that international students were challenged by social interactions, lack of English language proficiency and financial issues. The results of this study and their possible implications for educational institutions in Singapore and Asia are considered.